Some Arm Movement Variables Using Scattusb And Its Relationship With Shooting Accuracy For the Physically Disabled Sh1a) In 10m Air Pistol - Drwysh, Ammar; Farida, Ammar (Journal of Physical Education, 2017)
The accuracy of shooting depends on the human body movement specially the shooting arm. The aim of the research lies in identifying the relationship between arm movement variables and the accuracy of shooting using modern measurement devices and applying it to physical disabled shooters level Sh1a. One of the modern training devices is Scattusb due to its great effect on motor response. The researchers used the descriptive method, the subjects were (5) physically disabled shooters from the Iraqi national league. The researchers concluded that there is a relationship between some kinematical variables of the arm in physically disabled shooters of 10m air rifle